Design of an Integrated Visual Identity System for Mbarep Tour and Travel - Hanggo Titis Prasetyo; Fitro Nur Hakim (UNIVERSITAS STEKOM, 2026)
The tourism industry faced hyper-competition wherevisual identity became a vital asset, particularly ondigital platforms. Mbarep Tour and Travel struggledwith disintegrated visual management, resulting in alow engagement rate of 1.34 percent and significantinconsistencies in typography (70 percent). Thisresearch aimed to design an Integrated VisualIdentity System as a strategic solution for branddifferentiation. The Research and Developmentmethod was employed using a hybrid workflow thatintegrated CorelDRAW for vector precision, Geminiartificial intelligence for mascot three-dimensionalenhancement, and Canva for operational templates.The outcome was a comprehensive identity system,including refined logos, standardized typography,and a brand mascot, all codified in a GraphicStandard Manual. Post-implementation resultsshowed 100 percent effectiveness in resolving visualinconsistencies and increased the engagement rate to1.79 percent. This system successfully transformedthe brand into a more professional and competitiveentity.